2018
DOI: 10.1590/1678-992x-2016-0331
|View full text |Cite
|
Sign up to set email alerts
|

Automatically controlled deficit irrigation of lettuce in “organic potponics”

Abstract: Concerns with water crisis involve all sectors of society and irrigated agriculture remains the main water consumer. This study evaluated an agricultural production system for lettuce cultivation in greenhouse, "organic potponics", to economize water and manure use, using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
(41 reference statements)
2
17
0
2
Order By: Relevance
“…On leafs important physiological processes occur such as photosynthesis, respiration and transpiration. These processes are dependents of stomatal opening, which is closely correlated with soil moisture (Valença et al, 2018;Mu & Fang, 2017). Undoubtedly, the condition of high soil water depletion is unfavorable to growing of coriander.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On leafs important physiological processes occur such as photosynthesis, respiration and transpiration. These processes are dependents of stomatal opening, which is closely correlated with soil moisture (Valença et al, 2018;Mu & Fang, 2017). Undoubtedly, the condition of high soil water depletion is unfavorable to growing of coriander.…”
Section: Discussionmentioning
confidence: 99%
“…Under moderate soil water deficit, maybe the coriander produce more chlorophyll "a" in order to maximize the efficiency of solar radiation absorption or it is possible that occurs the effect of concentration due to the lower growth observed for the leafs (Valença et al, 2018). However, under severe soil water deficit can increase the degradation of chlorophyll "a" (Valença et al, 2018) as observed in arugula (Freitas et al, 2017) and sweet potato (Delazari et al, 2018). Low chlorophyll "a" means decreasing of photosynthesis efficiency and consequently, less biomass accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This device has been used in several field studies [ 17 ] and greenhouse studies [ 18 ], using different soils or substrates for plants. It is presented as an alternative in irrigation management [ 19 ] and has the advantage of being built with low cost materials [ 20 ]. Two actuators were used for each plant species studied, independently installed in two tubes with treatment corresponding to the highest flow rate (V4), totaling 6 actuators for the 3 experiments.…”
Section: Methodsmentioning
confidence: 99%
“…In a horticultural medium, Newby et al [42] used a Ψm ranging from −20 to −100 hPa as non-stressing conditions for growing flowers. Valença et al [43] indicated that Ψm ranging from −40 to −120 hPa caused water stress for papaya, but not for lettuce. For vegetable crops growing in a loamy sand, Bonachela et al [40] considered −100 to −200 hPa, −200 to −300 hPa and −300 to −500 hPa as high, conventional and low soil water availability, respectively.…”
Section: Water Stress Controlmentioning
confidence: 99%